The Rainbow Connection Number of Triangular Snake Graphs - Rocha, Aleffer; Almeida, Sheila M.; Zatesko, Leandro M. (Anais do Encontro de Teoria da Computação (ETC), 2020)
Rainbow coloring problems, of noteworthy applications in Information Security, have been receiving much attention last years in Combinatorics. The rainbow connection number of a graph G is the least number of colors for a (not necessarily proper) edge coloring of G such that between any pair of vertices there is a path whose edge colors are all distinct. In this paper we determine the rainbow connection number of the triple triangular snake graphs.